(untitled) (Research, Society and Development, 2023)
Introduction: The therapeutic approach to asthma is part of a vast confrontation within the scope of public health, given the fragility and vulnerability of this population group. Therefore, it is necessary to know the dynamics of attention to pediatric emergencies due to asthma attacks in children, analyzing their assumptions for appropriate care. Objective: to analyze the criteria for diagnosing and treating children with acute respiratory symptoms. Method: This is a qualitative, exploratory study, carried out through literature review research, in LILACS, PubMed and BVS Health databases using the descriptors “Asthma”, “Acute respiratory infections” and “Diagnosis and treatment”. Results: Asthma symptoms vary in terms of severity and frequency, and in terms of severity, they can cause daily chronic reactions and exacerbations. Exacerbation is the acute worsening of asthma symptoms. Treatment requires controlling daily symptoms and preventing exacerbations. There are therapeutic schemes for asthma control, such as, for example, the use of inhaled corticosteroids, associated with a decrease in the presence of asthma symptoms and exacerbations, reducing hospitalizations and deaths. Conclusion: Therapeutic effectiveness is associated with the correct use of medications with the safety of performing the appropriate inhalation technique, as well as directing a plan to control symptoms.